Coffee Marketing Mechanism: Social Relations Between Farmers, Collectors, Certification Cooperatives, and Exporters in Aceh, Indonesia - Andriadi Andriadi; Rizabuana Ismail; Fikarwin Fikarwin; Badaruddin Badaruddin; Ria Manurung; Henry Sitorus (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Several factors can influence the process of pricing mechanisms, namely competition between market participants, regulation, product quality, and consumer preferences. This is a challenge for Gayo Arabica coffee farmers, where coffee is the main commodity in Central Aceh Regency. This paper aimed to determine the social relations that occur between social actors (farmers, collectors, certification cooperatives and exporters) in the coffee marketing mechanism. This paper used a qualitative research method with a survey approach by conducting interviews with farmers, collectors, certification cooperatives and exporters. The results showed that the marketing of Gayo Arabica coffee involved several layers of actors. The coffee product marketing system can be done through two facilities, namely through export sales and domestic sales. There are differences in the income of coffee farmers in marketing coffee abroad or in the country where farmers benefit more from selling coffee products for exports. Relationship among actors are interdependent and bound. Farmers need collectors as tool providers and coffee price informans. Farmers follow cooperative certificates to get fair and more profitable prices.